Role of circRMRP and circRPL27 in chronic obstructive pulmonary disease - Li JianFang; Zhang PengFei; Zeng XianJing; Liu Rong (Open Life Sciences)
Chronic obstructive pulmonary disease (COPD) is one of the leading causes of death and disability worldwide, and circRNA dysregulation is functionally associated with COPD. This study explored the potential of circRMRP and circRPL27 as biomarkers of COPD. Blood samples from COPD patients and healthy controls were collected. COPD patients were divided into mild, moderate, and severe groups according to lung function. Quantitative real-time polymerase chain reaction technology was used to determine the expression of circRPL27 and circRMRP in COPD. Receiver operating characteristic curve was drawn to explore the value of circRMRP and circRPL27 in diagnosing COPD. circRMRP and circRPL27 levels were elevated in serum of COPD patients and increased with the severity of COPD. CircRMRP and circRPL27 were associated with smoking history, WBC, and FEV1/FVC, and were positively correlated with smoking history and WBC, and negatively correlated with FEV1/FVC. In COPD, both circRMRP and circRPL27 had diagnostic values, but circRPL27 was better. circRMRP and circRPL27 may be useful non-invasive biomarkers for COPD diagnosis.